Strategi Manajemen Pendidikan untuk Meningkatkan Kualitas Pendidikan di Era Digital - Desta Mayang Arum (SABA JAYA PUBLISHER, 2023)
Education in the digital era presents new challenges and opportunities for education management. This article discusses education management strategies that can be used to improve the quality of education in the digital era. This study uses a literature approach by collecting data from relevant theoretical sources on education management and digital technology in the educational context. This article outlines several educational management strategies that can be implemented, including the use of digital technology in teaching and learning, managing human resources in the digital era, developing curriculum that is relevant to technology, and implementing learning models that are appropriate to the digital era. This article also discusses the challenges and opportunities faced in implementing these strategies, including managing change, adaptive education policies, and developing teacher professionalism in the digital era. This study uses a literature approach, by collecting data from relevant theoretical sources on education management and digital technology in the educational context. Data is analyzed through a systematic synthesis of literature to identify education management strategies that can improve the quality of education in the digital era. In the digital era, an adaptive and technology-oriented education management strategy is the key to improving the quality of education. The use of digital technology in teaching and learning, managing human resources oriented towards the digital era, developing curriculum that is relevant to technology, and implementing learning models that are appropriate to the digital era are steps that can be taken to improve the quality of education in the digital era. However, challenges such as managing change, adaptive education policies, and developing teacher professionalism remain an important focus in the implementation of these strategies.